1984
DOI: 10.1083/jcb.98.3.877
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-mediated endocytosis in rat liver: purification and enzymic characterization of low density organelles involved in uptake of galactose-exposing proteins.

Abstract: Rat liver organelles involved in receptor-mediated endocytosis were labeled with a conjugate of galactosylated BSA to horseradish peroxidase ([3H]gaIBSA-HRP), injected 10 min before sacrifice . These organelles were recovered at low density (1 .11-1 .13 g/ml) in sucrose gradients (Quintart, J ., P. J. Courtoy, J. N . Limet, and P. Baudhuin, 1983, Eur. J. Biochem ., 131 :105-112) . Upon incubation of such low density fractions in 3,3'-diaminobenzidine (DAB) and H 202 and equilibration in a second sucrose grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 44 publications
2
37
0
Order By: Relevance
“…Other structures remained essentially at the initial low density, as indicated by the distributions of marker enzymes for the plasma membrane, lysosomes, and the Golgi complex (not shown) . The density distributions of these marker enzymes are presented in detail in the companion paper (24). Since the density shift induced by ga1BSA-HRP ("active" ligand) caused a concomitant density shift of ga1BSA ("passive" ligand), but not of other components, this experiment demonstrated that both derivatives were localized within the 874 THE IOURNAL OE CELL BIOLOGY " VOLUME 9S, 1984 same organelles.…”
Section: Concomitant Density Shift Of Two Ligandsmentioning
confidence: 86%
See 4 more Smart Citations
“…Other structures remained essentially at the initial low density, as indicated by the distributions of marker enzymes for the plasma membrane, lysosomes, and the Golgi complex (not shown) . The density distributions of these marker enzymes are presented in detail in the companion paper (24). Since the density shift induced by ga1BSA-HRP ("active" ligand) caused a concomitant density shift of ga1BSA ("passive" ligand), but not of other components, this experiment demonstrated that both derivatives were localized within the 874 THE IOURNAL OE CELL BIOLOGY " VOLUME 9S, 1984 same organelles.…”
Section: Concomitant Density Shift Of Two Ligandsmentioning
confidence: 86%
“…The specificity ofthe density shift to ligand-HRP containing structures was demonstrated by in vitro mixing experiments, a criterion already used by Leskes et al (19). In addition, only a minor portion of the protein shifted after cytochemistry, and the distribution of several marker enzymes present in the initial preparation was largely unaffected (24).…”
Section: Validity Of the Methodsmentioning
confidence: 99%
See 3 more Smart Citations